2011
DOI: 10.1111/j.1582-4934.2011.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and microRNAs: new direction in molecular epidemiology of solid cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs, which regulate gene expression. Single nucleotide polymorphisms (SNPs) may occur in miRNA biogenesis pathway genes, primary miRNA, pre-miRNA or a mature miRNA sequence. Such polymorphisms may be functional with respect to biogenesis and actions of mature miRNA. Specific SNPs were identified in predicted miRNA target sites within 3′ untranslated regions of mRNAs. These SNPs have a potential to affect the efficiency of miRNA binding to the target sites or can create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 81 publications
(129 reference statements)
0
75
0
2
Order By: Relevance
“…To the best of our knowledge, the present study is the first combined clinical and cell functional study of the association between rs11614913 SNP and susceptibility to ovarian cancer. It is widely accepted that gene variants located in pri-and pre-miRNA regions may influence the biological functions of miRNAs and eventually lead to alterations in disease incidence (32). Considering this, various studies have investigated the application of pri-and pre-miRNA polymorphisms as predictors of cancer risk (29,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first combined clinical and cell functional study of the association between rs11614913 SNP and susceptibility to ovarian cancer. It is widely accepted that gene variants located in pri-and pre-miRNA regions may influence the biological functions of miRNAs and eventually lead to alterations in disease incidence (32). Considering this, various studies have investigated the application of pri-and pre-miRNA polymorphisms as predictors of cancer risk (29,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs895819, located in pre-miR-27a, was evaluated in an association study in which SNPs located in recently identified breast cancer-relevant miRNA genes were examined (including pre-miRNAs and an approximately 200-base pair flanking region) by sequencing of these regions (Slaby et al, 2012). In a group of 1217 German familial breast cancer patients and 1422 unrelated healthy German women, Yang et al (2010) found that the G allele of rs895819, located in the terminal loop of a pre-miR-27a oncogene, was associated with a reduced familial breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are located within introns or exons of protein-coding genes and in intergenic regions. In addition, miRNAs have been found in many areas of the genome which are associated with cancer development: fragile sites, regions of amplification and LOH regions [11,36,42].…”
Section: Introductionmentioning
confidence: 99%